An efficient Grain-80 stream cipher with unrolling features to enhance the throughput on hardware platform - Raghavendra Ananth; Panduranga Rao Malode Vishwanatha Rao; Narayana Swamy Ramaiah (Institute of Advanced Engineering and Science, 2024)
The stream cipher is a fundamental component of symmetric cryptography and offers unique implementation speed and scalability advantages. Additionally, the complexity of the cipher algorithm deployment environment forces new, appropriate designs and challenges on the already-existing cipher algorithms. To increase throughput, an efficient Grain-80 stream cipher with unrolling features is designed in this manuscript. The Grain-80 cipher uses an 80-bit key, and a 64-bit initialization vector (IV) and contains two feedback shift registers (linear and non-linear) and an output function. The register balancing and unrolling features of the proposed Grian-80 cipher combine to increase throughput while requiring little additional hardware. Low latency, fast throughput, excellent efficiency, and reduced attack susceptibility are all features of the unrolling architecture. The proposed Grain-80 cipher utilizes <1% chip area and operates at 542.7 MHz on Artix-7 field programmable gate array (FPGA). The proposed Grain-80 cipher improves the operating frequency by 14.85% over conventional Grain-80 cipher. The Grain-80 cipher obtains the throughput of 4.35 Gbps and 8.69 Gbps for unrolling factors 8 and 16, respectively. Lastly, the proposed Grain-80 cipher is compared with existing Grain-80 ciphers with improved throughput and hardware efficiency.